URGENSI PERLINDUNGAN HUKUM TERHADAP PENCIPTA KARYA ILMIAH DARI TINDAK PIDANA PENCEMARAN NAMA BAIK - Frinaldi Samuel Sirait; Erdiansyah Erdiansyah; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
With the rapid development of technology, the law must also be able to keep up withtechnological developments and the times, but this advancement in information technology hasnegative consequences for creators of scientific works, this is because there are no specificlaws or rules that can protect creators of scientific works from accusations of defamation, sofar many creators of scientific work have been subject to defamation articles related to theirscientific work. Criminal sanctions should be used as a last resort in resolving a legal issue,this is in accordance with the principle of ultimum remedium, there should be other sanctionsimposed on the creation of scientific works if the scientific work is deemed incorrect.This study uses a normative juridical research type, namely research that is focused onexamining the application of the rules or norms in law to legal principles. The data collectiontechnique in this research is literature study. The approach used in this research is to use anormative approach, namely library law research.The results of the research conducted by the author are first, the urgency of legalprotection for creators of scientific works from accusations of defamation can be said to beurgent/important, this is because scientific works are the result of studies or scientific facts inthe field and also so far there are many creators of works science which is sanctioned bycriminal law.Secondly, in overcoming problems related to the large number of creators of scientificworks who are charged with defamation, regulations are needed that regulate legal protectionfor creators of scientific works. Suggestions in resolving the problem regarding the largenumber of creators of scientific works being subject to defamation sanctions, the governmentand the House of Representatives must form a law to provide legal protection for creators ofscientific works.Keywords: Defamation, Creator of Scientific Work.